The effect of group investigation model assisted by interactive media Lectora Inspire on high school students critical thinking skills - Aulia Nindy Fadila Gastama; Fatiya Rosyida; Budi Handoyo; Djoko Soelistijo (Universitas Negeri Yogyakarta, 2023)
Geography learning teaches students to be able to think critically. Critical thinking is one of the thinking skills that students must have in 21st-century learning. However, the critical thinking skills of high school students in Indonesia are proven to be lacking. The study aimed to determine the effect of the Group Investigation (GI) model assisted by interactive media Lectora Inspire on high school students' geography critical thinking skills. The research design used a quasi-experimental design with a posttest-only control group design. The location of the research was carried out at the Laboratory Senior High School Universitas Negeri Malang. The research subjects were XI IPS 3 students as the experimental group and XI IPS 1 as the control group. Data on students' critical thinking skills were obtained from six essay test questions arranged according to indicators of critical thinking skills. Data analysis techniques for critical thinking skills using the Mann-Whitney test show that the GI model assisted by interactive media Lector Inspire affects high school students' critical thinking skills. Comparison of the post-test scores of the experimental group is much better than the control group. The steps of the GI model and interactive media Lectora Inspire during learning to make students productive in critical thinking.